Protein profiling of conjunctival impression cytology samples of aniridia subjects - Stachon, Tanja; Fecher‐Trost, Claudia; Latta, Lorenz; Yapar, Dalya; Fries, Fabian N.; Meyer, Markus R.; Käsmann‐Kellner, Barbara; Seitz, Berthold; Szentmáry, Nóra (Acta ophthalmologica (Oxford, England), 2024)
Purpose Congenital aniridia is a rare disease, which is in most cases related to PAX6 haploinsufficiency. Aniridia associated keratopathy (AAK) also belongs to ocular signs of congenital aniridia. In AAK, there is corneal epithelial thinning, corneal inflammation, vascularization and scarring. In advanced stage AAK, typically, conjunctival epithelial cells slowly replace the corneal epithelium. Based on previous results we hypothesize that alterations of the conjunctival cells in congenital aniridia may also support the corneal conjunctivalization process. The aim of this study was to identify deregulated proteins in conjunctival impression cytology samples of congenital aniridia subjects. Methods Conjunctival impression cytology samples of eight patients with congenital aniridia [age 34.5 ± 9.9 (17–51) years, 50% female] and eight healthy subjects [age 34.1 ± 11.9 (15–54) years, 50% female] were collected and analysed using mass spectrometry. Proteomic profiles were analysed in terms of molecular functions, biological processes, cellular components and pathway enrichment using the protein annotation of the evolutionary relationship (PANTHER) classification system. Results In total, 3323 proteins could be verified and there were 127 deregulated proteins (p < 0.01) in congenital aniridia. From the 127 deregulated proteins (DEPs), 82 altered biological processes, 63 deregulated cellular components, 27 significantly altered molecular functions and 31 enriched signalling pathways were identified. Pathological alteration of the biological processes and molecular functions of retinol binding and retinoic acid biosynthesis, as well as lipid metabolism and apoptosis related pathways could be demonstrated. Conclusions Protein profile of conjunctival impression cytology samples of aniridia subjects identifies alterations of retinol binding, retinoic acid biosynthesis, lipid metabolism and apoptosis related pathways. Whether these changes are directly related to PAX6 haploinsufficiency, must be investigated in further studies. These new findings offer the possibility to identify potential new drug targets.